HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL SHOOTING PADA TIM BOLA BASKET PUTRA SMA NEGERI 3 PEKANBARU - Febriansyah, Rahmat Febriansyah; Juita, Ardiah Juit; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this study originated from the observation that the authors found in the field, basic skills of the men's basketball team SMA N 3 Pekanbaru is not good that the ability of shooting (shot) and the authors suspect the cause is a physical condition that is less supportive. The purpose of this study was to determine the relationship of explosive power arm and shoulder muscles with the shooting at the men's basketball team SMA N 3 Pekanbaru. The population in this study was the men's basketball team SMA N 3 Pekanbaru, amounting to 10 people using the total sampling technique where all the population sampled, to obtain research data of explosive power arm and shoulder muscles used tests of two-hand medicine ball put, and the results freethrow shooting for 1 minute. Data were analyzed with a simple product moment. Based on the results of research and data processing using statistical procedures of research it can be concluded that for the relationship variable x to variable y categorized as low, thus Ho is accepted by rarithmetic = 0.25 <of rtable = 0.666. In conclusion the hypothesis is accepted at significance level α of 0.05, in other words the low explosive power relationship exists between the arm and shoulder muscles with the shooting at the men's basketball team SMA N 3 Pekanbaru.Keyword : Explosive Power Arm and Shoulder Muscles, Shooting Results Freethrow.